How labour ended up taxing itself: the political consequences of a century of self-transformation of the German welfare state - Achim Kemmerling (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
This paper investigates the long-term evolution of the tax system in Germany to explain why the political left has increasingly expanded taxation to its own clientele. The paper contrasts the second half of the 19th with the second half of the 20th century to show that some of the underlying parameters of tax systems have changed over time. In particular these are the existence of a mature welfare state and the significance of real wages as a tax base. Moreover, the paper selectively uses comparisons with the United Kingdom (UK) to show that where these conditions are absent the structure of the tax system is very different and taxes labour much less than in Germany. In this sense the British selftransformation of the welfare state has had very different political consequences than the German ; Das Diskussionspapier untersucht die langfristige Entwicklung des Steuersystems in Deutschland und erklärt, warum die politische Linke sich in zunehmendem Maße selbst besteuert. Dazu werden die zweiten Hälften des 19. und 20. Jahrhunderts miteinander verglichen, um zu zeigen, dass die zugrunde liegenden Rahmenbedingungen des Steuersystems sich verändert haben. Zu letzteren zählen insbesondere der Wohlfahrtsstaat und die Reallöhne als Steuerbasis. Zudem werden Vergleiche mit der Entwicklung im Vereinigten Königreich gezogen. Dadurch wird deutlich, dass, wo diese Rahmenbedingungen sich anders entwickelt haben, sich auch das Steuersystem anders entwickelte, und dass vor allem Arbeitnehmer weniger besteuert werden. In diesem Sinne hatte die Selbsttransformation des britischen Wohlfahrtsstaates ganz andere politische Konsequenzen als die deutsche.
Keywords: 330; Lohnsteuer; Steuersystem; Steuergeschichte; Sozialstaat; Sozialreform; Deutschland; Großbritannien